Analisis Efektivitas Pengendali Biaya Produksi Pada Pt. Daur Ulang Sejahtera (Dsa) Di Bandar Lampung (Study Kasus pada PT Daur Ulang Sejahtera (DSA) di Bandar Lampung) - . Thontowi; . Yeni; Syamsu Rizal (Jurnal Akuntansi dan Keuangan, 2012)
PT DSA is a company engaged in the industry which produces plastic ore used as the main ingredient manufacture of household appliances. Problems faced by PT DSA are: the presentation of information in terms of ore production cost of plastic, in which top management as users can not report quickly and accurately obtain the required data in decision-making. And the problem is formulated: "How Implementation Effectiveness Production Cost Control at PT DSA?" In the discussion of the data analysis section, it can be concluded that the results of research at PT DSA responsibility accounting is used for cost control has not been implemented effectively. It can be seen from the budgeting process and who is responsible for reporting on the implementation of the work that has been accomplished. Manufacturing cost reporting systems can still be used to assess the performance, efficiency and effectiveness of each department for the report did not provide a comparison between the budget and expenses. And PT DSA in preparing budget reports do not separate the cost of production with a controllable costs uncontrollable. As well as the PT DSA, there are departments that have the dual task of making the department that has the double task becomes ineffective. In order for the accounting responsibility on PT DSA can run effectively, it should have a separation of functions of employees to run operations effectively, and preferably in preparing the production budget to separate between production costs can be controlled with uncontrollable. As well as in preparing the production budget includes an entire head of departments.